Maniobra Kristeller, consecuencias físicas y éticas según sus protagonistas - Becerra-Chauca, Naysha (2019)
ABSTRACT: Introduction: The Kristeller maneuver consists in making fundal pressure during the second stage of labor. Objective: To determine the prevalence, characteristics of the application of Kristeller maneuver and the physical and ethical consequences in puerperal women of a highly complex hospital in Lima, Peru. Methods: A cross-sectional and prospective descriptive study was carried out in 250 puerperal women of vaginal delivery, with single gestation at term, assisted at Hipólito Unanue National Hospital, from August to December 2016. This research used the Stop Kristeller questionnaire - prepared by the Spanish Association “El parto es nuestro”. A questionnaire validated by experts was applied to the puerperal women during their stay. A descriptive analysis was made and the results in frequencies and percentages are shown. Results: It was showed that 116 of them (46.4 %) underwent Kristeller maneuver. Regarding the characteristics of the maneuver performance, 77.6 % reported that it was performed with hand palms, more than 70 % reported that this maneuver was done between one and three times and 75.9 % indicated that only one person performed it. Vaginal tear was reported in 32.8 % and 51.7 % reported their consent to perform the maneuver was not requested. Conclusions: There is high prevalence of the use of this maneuver. The characteristics of its application follow the guidelines described by Samuel Kristeller. Superficial and deep perineal tears are among the physical consequences and in many cases, bioethical conditions were not fulfilled.